What policies are needed to counter the commercial determinants of health? - Claudio Schuftan; Angela Carriedo (Social Medicine Publication Group, 2023)
This commentary aims to bring up to the attention of the reader the relevance and key role of activists in countering the commercial determinants of health. We suggest some strategies   and key activities for activists. We also highlight the multiple challenges activists will (and have) undoubtedly face(d).   We integrate a few examples pertaining to these points to exemplify what we mean here and why we are being harsh in the language we use and/or the actions we propose. There are multiple experiences hinting the way on how activists encompassing several fields ought to be going ahead.